Practical Strategies for Library Managers - Joan Giesecke (American Library Association., 2001)
Are you feeling caught in the middle? Do you feel you have many responsibilities? Do you feel that you have to answer to everyone? Do today’s top managers seem determined to eliminate your level of the organization? If you are feeling overwhelmed as a manager or department head, you are not alone. Your colleagues are likely to be just as frustrated and concerned. But don’t despair. Today’s middle managers are crucial for holding the organization together. This group helps tie frontline staff to top management. You provide the working leadership for the organization, helping to translate the overall organizational vision into the work of the department, unit, or team. You help link your group to the other units in the organization. For today’s middle manager, the challenge is not in finding a meaningful position in the organization. Rather, the challenge is to develop practical strategies you can use to help your unit achieve its goals while helping the organization reach its vision. Most management books address the needs of top managers and leaders. Few books examine the complex role of the middle manager. But this book is designed to help you in your management role. It outlines strategies you can use to successfully manage your unit whether you are called a department head, team leader, or unit head. The first two vii Preface chapters provide an overview of the changing world of today’s managers. Chapter 3 outlines the many new roles you will play in the organization. These include: Leadership role Facilitator role Working leader role Catalyst role In chapter 4, you will learn how to succeed as a new department team leader or unit head. Taking charge of a new department or unit requires careful planning and cannot be left to chance. How you begin your job will greatly affect how well you are accepted by your team or unit. The next four chapters concentrate on the management skills you will need as a manager. While first line supervisors spend much of their time coordinating work and handling interpersonal relationships, managers must add mentoring, planning, and decision-making skills to their repertoire. Of course, good communication skills are essential and middle managers need to ensure that they continually improve their skills in this area. Finally, chapter 9 describes various ways to organize the department while chapter 10 helps tie the various strategies together for you. Being a middle manager is a challenging and rewarding experience. This book will provide you with various practical strategies and skill sets you can use to make your position successful and enjoyable. I wish to acknowledge the help of my colleagues and my office in putting this book together. We hope that both managers and mentors will find these strategies useful.